2022
DOI: 10.3390/plants11040544
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analyses of Aspartic Proteases on Potato Genome (Solanum tuberosum): Generating New Tools to Improve the Resistance of Plants to Abiotic Stress

Abstract: Aspartic proteases are proteolytic enzymes widely distributed in living organisms and viruses. Although they have been extensively studied in many plant species, they are poorly described in potatoes. The present study aimed to identify and characterize S. tuberosum aspartic proteases. Gene structure, chromosome and protein domain organization, phylogeny, and subcellular predicted localization were analyzed and integrated with RNAseq data from different tissues, organs, and conditions focused on abiotic stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 104 publications
(204 reference statements)
0
3
0
Order By: Relevance
“…For example, aspartic-type endopeptidases (cluster 6) have been associated with plant defense response mechanisms, hybrid sterility, reproductive development, abiotic and biotic stresses, chloroplast homeostasis, and lateral root development [ 48 ]. It has been shown that segmental and tandem duplications are characteristic of genes in this group in the potato genome, and the expression of approximately 21% of these genes changes under salt, osmotic, or temperature treatments [ 49 ]. Genes from the 3 rd functional cluster (replication factor A) are also shown to change expression associated with endoplasmic reticulum stress and potential involvement in genotoxic stress responses [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, aspartic-type endopeptidases (cluster 6) have been associated with plant defense response mechanisms, hybrid sterility, reproductive development, abiotic and biotic stresses, chloroplast homeostasis, and lateral root development [ 48 ]. It has been shown that segmental and tandem duplications are characteristic of genes in this group in the potato genome, and the expression of approximately 21% of these genes changes under salt, osmotic, or temperature treatments [ 49 ]. Genes from the 3 rd functional cluster (replication factor A) are also shown to change expression associated with endoplasmic reticulum stress and potential involvement in genotoxic stress responses [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Though A1 aspartic protease family members have been identified and described by different investigators in last two decades, the gene number of A1 family ranges from 51 to 69 (Beers et al, 2004;Faro and Gal, 2005;Takahashi et al, 2008;Wang et al, 2019;Yu et al, 2021). To obtain as many A1 members as possible in Arabidopsis, the HMM profile of ASP domain (PF00026), which has been used to identify A1 family genes in rice (Chen et al, 2009), grape (Guo et al, 2013), poplar (Cao et al, 2019), wheat (Yang and Feng, 2020), moso bamboo (Wang et al, 2021) and potato (Norero et al, 2022), was used as a query to identify AP genes in the first round search. Then only 64 genes were identified (Table S1), which is obviously underestimated since reported aspartic proteases such as SAP1(AT1G03220) and SAP2(AT1G03230) cannot be not identified (Wang et al, 2019).…”
Section: A1 Aspartic Protease Content In Arabidopsis Genomementioning
confidence: 99%
“…Aspartic proteases, commonly known as acid proteases or aspartyl proteases, are classified as hydrolases (group 3) within subgroup 4, which can hydrolyze peptide bonds. They are diversely found in living organisms as well as in viruses (Norero et al., 2022). They are endopeptidases that use an activated water molecule bound to one or two aspartate residues for catalysis.…”
Section: Introductionmentioning
confidence: 99%